Descrição de Astyanax argyrimarginatus sp. n. (Characiformes, Characidae) procedente da bacia do Rio Araguaia, Brasil - GARUTTI, V. [UNESP] (Instituto Internacional de Ecologia, 1999)
Descreve-se uma espécie nova para o gênero Astyanax Baird & Girard. A. argyrimarginatus procede da bacia do Rio Araguaia, Brasil. Esta espécie pode ser identificada por possuir uma mancha umeral negra horizontalmente ovalada, uma mancha negra no pedúnculo caudal, que se estende à extremidade dos raios caudais medianos, duas barras verticais castanho-escuras na região umeral e uma faixa lateral negra conspícua, bordeada por uma estreita faixa prateada. São discutidos outros caracteres que distinguem a espécie nova das demais espécies do gênero Astyanax portadoras de uma mancha umeral horizontalmente ovalada.

Astyanax argyrimarginatus sp. n. is described from the Araguaia River basin, Brazil. The new species may be diagnosed by a humeral dark spot horizontally oval, and an elongated caudal peduncle dark spot, continued to the tip of the mid caudal rays, two dark brown vertical bars on the humeral region, and a single black lateral stripe with silvered border. Forty-two to forty-six scales on lateral line; fourteen to sixteen vertical scales rows. Twenty-seven to thirty-one anal fin rays. Dentary large teeth quincuspid, inner row of pre-maxilar teeth quincuspid or hexacuspid, and one maxillary tooth. Comments on the characters which permit to recognize the new species from others with the same color pattern are made.
Description of a new species of the genus Astyanax Baird & Girard from Araguaia River basin, Brazil
Keywords: Astyanax argyrimarginatus sp. n.; Characidae; Tetragonopterinae; taxonomia; descrição; Rio Araguaia; Brasil; Astyanax argyrimarginatus sp. n.; Characidae; Tetragonopterinae; taxonomy; description; Araguaia River; Brazil